(untitled) (Bangladesh Journal of Medical Science, 2025)
Piezoelectric surgery is a boon to periodontics, providing increased control and safety during various periodontal surgeries. Piezoelectric devices perform selective hard tissue cutting while the surrounding soft tissues experience minimal trauma due to ultrasonic vibrations. The current development and progression of piezosurgery in periodontal therapy have been thoroughly discussed in this paper. This review explores piezoelectric technology and examines its effects on clinical outcomes, including patient comfort, hospitalization duration, healing time, and procedure efficacy, compared to conventional surgeries. The review overviews current research findings and highlights benefits such as decreased thermal damage, enhanced tissue preservation, and increased visual field during surgery. Furthermore, it addresses the limitations and potential concerns with piezosurgery, expense, and the practitioner learning curve. Moreover, it aims to address the limitations and potential concerns with piezosurgery, cost, and the practitioner learning curve. It is intended to offer a more nuanced view on incorporating piezoelectric surgery in periodontal therapy and forecast future directions by evaluating the current evidence and individual clinical experience. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 362-372